موجودہ دور میں سائنسی علوم کے تناظر میں قرآنی تفسیر: Quranic Exegesis in the Light of Contemporary Scientific Perspectives - Dr. Abdul Majid; Dr. Sayyed Azkia Hashimi (MEI, 2023)
There exists mainly two viewpoints pertaining to exegesis of the holy Quran. According to one viewpoint Quranic exegesis (Tafseer) can be done in the light of modern disciplines of Knowledge including modern science. The other viewpoints does not endorse the Quranic exegesis in modern perspectives. The current paper will explore the viewpoint that whether the Quranic exegesis is permissible and appropriate in the light of modern scientific and intellectual thoughts. Unde this viewpoint few scholars will be quoted to see the critical point of interpreting cosmological verses in the light of modern scientific data.Scientific and intellectual knowledge is only possible due to intellect or aql, so importance of intellect and intellectual arguments is elaborated to authenticate the viewpoint. The holy Quran contains about 750 verses alluding to the phenomena of nature which are scattering in the heavens and the earth. All these phenomena are deemed as signs of Almighty Creator as they are His creation.The Quran considers phenomena of nature in afaq –o- anfus as cosmological signs (ayat) as it says to its verses as signs. Both verbal & non-verbal (Physical) signs are given the same importance in the holy Quran. So explaining those ayat in the light of modern science is nothing but the main purpose of the Quran as the holy Quran was not only for the previous generations but for all generations to satisfy them. That satisfaction can be achieved only in the language of modern man and in the context of modern science which can quench the thirst of modern mind. Luckily all those signs and themes are present in the Quran. Now just need to be expressed in the light of modern sciences which is main theme of the current paper.